2014
DOI: 10.1021/bi500289h
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Glycine 232 in the Ligand Channel of ba3 Cytochrome Oxidase from Thermus thermophilus

Abstract: Knowing how the protein environment modulates ligand pathways and redox centers in the respiratory heme-copper oxidases is fundamental for understanding the relationship between the structure and function of these enzymes. In this study, we investigated the reactions of O2 and NO with the fully reduced G232V mutant of ba3 cytochrome c oxidase from Thermus thermophilus (Tt ba3) in which a conserved glycine residue in the O2 channel of the enzyme was replaced with a bulkier valine residue. Previous studies of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 43 publications
4
18
0
Order By: Relevance
“…In contrast, the inferred pathway from X-ray data for O 2 diffusion to the active site of cytochrome ba 3 is supported by both previous experimental data and by MD simulations, which only concentrated on the dynamics and stability of O 2 binding at individual X-ray Xe sites, 33,34 as well as the present study. The tunnel in this B-family heme-copper oxygen reductase does not have the constriction observed in the A-family enzymes.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In contrast, the inferred pathway from X-ray data for O 2 diffusion to the active site of cytochrome ba 3 is supported by both previous experimental data and by MD simulations, which only concentrated on the dynamics and stability of O 2 binding at individual X-ray Xe sites, 33,34 as well as the present study. The tunnel in this B-family heme-copper oxygen reductase does not have the constriction observed in the A-family enzymes.…”
Section: Discussionsupporting
confidence: 81%
“…Short (1 ns) MD simulations showed that there is effectively no barrier within this tunnel for O 2 diffusion. 34 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subunit II of COX contains a Cu A redox centre, serves as a binding partner for cytochrome c, and as a participant in the electron transfer process [86]. Subunit II has a highly conserved glycine residue at the active site [87][88][89]. A mutant form of COX in Rhodobacter sphaeroides involving a substitution of valine for the conserved gly283 resulted in a complete block of access of oxygen to the active site [88].…”
Section: Cytochrome C Oxidasementioning
confidence: 99%